2019
DOI: 10.1155/2019/8173808
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentrism, Trust, and the Willingness to Pay of Chinese Consumers for Organic Labels from Different Countries and Certifiers

Abstract: Although numerous studies have examined consumer preference for organic foods, few have focused on consumer willingness to pay (WTP) for organic labels from dissimilar countries or certifiers. We conducted a choice experiment to examine how Chinese consumer ethnocentrism and trust on organic labels and certifiers may affect their WTP for organic labels from different countries as well as for different certifiers. Chinese consumers did not show a high level of ethnocentrism, and this may lead to inconsistencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
(54 reference statements)
4
16
0
1
Order By: Relevance
“…In particular, we examined the role of food certifications to better understand consumer awareness of their existence and consumer preferences for food safety information attributes. The limited literature [ 29 , 64 ] and its controversial results [ 12 ] reflect the uncertainty in China on this issue, but this information is central for policymakers and the food industry. Our research confirmed that certifications play no clear role in the food safety choices in consumers at large.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we examined the role of food certifications to better understand consumer awareness of their existence and consumer preferences for food safety information attributes. The limited literature [ 29 , 64 ] and its controversial results [ 12 ] reflect the uncertainty in China on this issue, but this information is central for policymakers and the food industry. Our research confirmed that certifications play no clear role in the food safety choices in consumers at large.…”
Section: Discussionmentioning
confidence: 99%
“…Japan is the largest importer of Chinese Oolong tea, so companies are inclined to use Japanese organic labels (JAPLs) for export to Japan. Several recent studies have demonstrated that Chinese consumers showed a higher preference for organic labels from developed countries (Chen et al, 2019a;Yin et al, 2019a). In this research, the US organic label (USL) was chosen as the representative to examine consumer attitudes.…”
Section: Attribute Selectionmentioning
confidence: 99%
“…Chinese food safety scandals have led to market chaos, which resulted in distrust of domestic organic labels (Wu et al, 2014). Therefore, organic labels from other regions are prevalent in the Chinese organic market (Yin et al, 2019a). With organic labels of different regions coexisting in the Chinese market (Yin et al, 2019a), the attitudes toward various organic labels have emerged in a few studies, and the results indicate that Chinese consumers prefer organic labels from more developed regions (Li et al, 2015;Yin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Karahan Uysal et al [71]; Janssen and Hamm [72]; Richetin et al [73]; Meyerding and Merz [74]; Yin et al [75]; Parker et al [76], Study 1a; Gaylord et al [77]) compared products with several organic label variants, rather than products with no (or a conventional) label and those with an organic label; i.e., they examined whether there is a difference in consumers' evaluation as a result of the type of label on the product, not the effect of the organic label. The examination by Mather et al [78], Gifford and Bernard [62], and Onken et al [22] had a similar setting, with the difference that instead of comparing various organic label types, they involved labels connected to more diverse production systems (e.g., natural, free-range, not GM fed).…”
Section: Methodsmentioning
confidence: 99%